Development of Ca(2+) hotspots between Lymnaea neurons during synaptogenesis - Feng, Zhong-Ping (Blackwell Science Inc, 2002)
Calcium (Ca(2+)) channel clustering at specific presynaptic sites is a hallmark of mature synapses. However, the spatial distribution patterns of Ca(2+) channels at newly formed synapses have not yet been demonstrated. Similarly, it is unclear whether Ca(2+) ‘hotspots’ often observed at the presynaptic sites are indeed target cell contact specific and represent a specialized mechanism by which Ca(2+) channels are targeted to select synaptic sites. Utilizing both soma–soma paired (synapsed) and single neurons from the mollusk Lymnaea, we have tested the hypothesis that differential gradients of voltage-dependent Ca(2+) signals develop in presynaptic neuron at its contact point with the postsynaptic neuron; and that these Ca(2+) hotspots are target cell contact specific. Fura-2 imaging, or two-photon laser scanning microscopy of Calcium Green, was coupled with electrophysiological techniques to demonstrate that voltage-induced Ca(2+) gradients (hotspots) develop in the presynaptic cell at its contact point with the postsynaptic neuron, but not in unpaired single cells. The incidence of Ca(2+) hotspots coincided with the appearance of synaptic transmission between the paired cells, and these gradients were target cell contact specific. In contrast, the voltage-induced Ca(2+) signal in unpaired neurons was uniformly distributed throughout the somata; a similar pattern of Ca(2+) gradient was observed in the presynaptic neuron when it was soma–soma paired with a non-synaptic partner cell. Moreover, voltage clamp recording techniques, in conjunction with a fast, optical differential perfusion system, were used to demonstrate that the total whole-cell Ca(2+) (or Ba(2+)) current density in single and paired cells was not significantly different. However, the amplitude of Ba(2+) current was significantly higher in the presynaptic cell at its contact side with the postsynaptic neurons, compared with non-contacted regions. In summary, this study demonstrates that voltage-induced Ca(2+) hotspots develop in the presynaptic cell, concomitant with the appearance of synaptic transmission between the soma–soma paired cells. The appearance of Ca(2+) gradients in presynaptic neurons is target cell contact specific and is probably due to a spatial redistribution of existing channels during synaptogenesis.